Системи моніторингу та аудиту задля забезпечення захисту від втрати даних - Бринза, І. Ю.; Желєзнякова, В. В. (ХНУРЕ, 2025)
Modern corporate data loss prevention (DLP) systems are becoming increasingly in demand as organizations need to process larger amounts of their clients' information. DLP systems are based on the creation of policies and rules for filtering outbound traffic. Their goal is to minimize the number of successful data transmissions. It has been established that the most effective protection is provided by comprehensive security systems that prevent data leaks through various channels, including email, web resources, USB devices, third-party applications, and printers.
Keywords: втрата даних; захист від втрати даних